Systematic Literature Review: Analysis of Factors Influencing Interest Purchasing Halal Cosmetics 2018-2024 - Rizqillah, Adika Iftitah; Ainiyah, Maf Ulatul; Ariyati, Izza Milenia; Hakim, Luqman (Journal of Islamic Economic Laws, 2025)
This research aims to analyze the factors influencing the intention to purchase halal cosmetics and to identify research trends in this sector from 2018 to 2024. Using the Systematic Literature Review (SLR) method guided by the PRISMA framework, this study systematically collects and analyzes data from scientifically indexed articles to provide a comprehensive understanding of consumer behavior towards halal cosmetics. The findings indicate a significant rise in publications on halal cosmetics, with research interest peaking in 2024. Key factors influencing purchasing decisions include awareness of product safety, halal certification, and lifestyle preferences. Furthermore, the study highlights that most existing research focuses on Muslim consumers, while the perspectives and motivations of non-Muslim consumers remain underexplored. This research contributes to the advancement of knowledge in halal cosmetic studies by mapping existing literature and identifying gaps for future research. It provides valuable insights for producers in designing more effective marketing strategies and supports policymakers in developing consumer protection regulations. Strengthening the position of halal cosmetics in the global market, this study also emphasizes the importance of educating consumers on sharia-compliant product choices. Future research is recommended to explore the motivations and perceptions of non-Muslim consumers and the impact of halal certification on consumer loyalty.